Characterization of fiscal sacrifice and the importance of incorporating its cost in the public budget process: a phenomenological approach - Monasterio-Pérez, Johnny; Rincón Soto, Idana Beroska (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This paper reveals that the characterization of tax sacrifice depends on the interdisciplinary treatment given to the issue of tax expenditures and tax benefits. The feelings of subjects with experience in this matter are expressed, providing interpretations to the following questions: How can tax sacrifice be characterized in the regulatory framework of the Venezuelan context? Which tax benefits are considered tax expenditures? In order to answer this question, it is proposed that tax sacrifice comprises an economic effort by the State that affects the development of certain economic sectors and the fulfillment of social objectives aimed at improving the collective welfare. The methodology assumed is of a dialogic nature, from Husserl’s phenomenology (1997), as an approach and method, which tries to understand, in an immediate way, the world of man through an intellectual vision based on the intuition of the thing itself. The instruments used for the collection of information are represented by semi-structured interviews applied to key informants, as well as a structured intentional analysis matrix (Krippendorff, 1990) according to the dimensions of the study. In closing, the following categories were revealed: Phenomenological characterization of tax sacrifice; Effects of tax sacrifice on the budget formulation process; and, Identification of the approach to define reference taxes and tax expenditures present in the national taxation regulatory framework.